2008
DOI: 10.1055/s-2008-1059379
|View full text |Cite
|
Sign up to set email alerts
|

Q-Fieber-Epidemie in Berlin: Epidemiologische und klinische Aspekte

Abstract: An epidemic of Q fever in Berlin affected at least 80 patients (45 females, 35 males; age range 1-75 years). Sheep were identified as the focus of infection: they had been brought to a veterinary clinic because of nonspecific symptoms. The peak incidence of the infection was in April and May, 1992. Most of the patients were staff or students at the veterinary clinic. This is the most northern and, at the same time largest, Q fever epidemic recorded in Germany over the last 28 years. The complement fixation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The overall prevalence of anti-Coxiella antibodies in the people studied to date in China is 10•2% (1139/11 209) ( Table 3). The sensitivities of the CFT and IFA seem to be similar in people with a prevalence of 10…”
Section: Overview Of Q Fever In Chinamentioning
confidence: 92%
“…The overall prevalence of anti-Coxiella antibodies in the people studied to date in China is 10•2% (1139/11 209) ( Table 3). The sensitivities of the CFT and IFA seem to be similar in people with a prevalence of 10…”
Section: Overview Of Q Fever In Chinamentioning
confidence: 92%
“…Seroepidemiological surveys have shown that 18.3% of blood donors in Morocco, 26% in Tunisia [52], 37% in Zimbabwe [53], 44% in Nigeria [54], 10 to 37% in northeast Africa, and 14.6 to 36.6% in different areas of Canada [22] had anti- C. burnetii antibodies. Large outbreaks of Q fever have also been reported in the Basque country in Spain [55], in Switzerland [56], in Great Britain [57], and in Berlin, Germany [58]. …”
Section: Epidemiologymentioning
confidence: 99%
“…Q fever has outbroken in people in some countries, including Spain [ 8 ], Switzerland [ 9 ], Great Britain [ 10 ], Germany [ 11 ], and Netherlands [ 12 ]. Infections are usual occupational risk in persons working with livestock and contacting with highly infectious aerosols from birth products, milk, urine, faeces, or semen of infected animals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%